press on nail, water marble, dra Perbandingan Teknik Water Marble Dengan Drawing Marble Pada Hasil Jadi Press On Nails di Faux Nail Studio - Nofitasari, Sonia; Kecvara Pritasari, Octaverina; Kusstianti, Nia; Megasari, Dindy Sinta (Program Studi Pendidikan Tata Rias, 2025)
In the last five years, marble nail art has become a trend that is increasingly in demand by nail art lovers. The purpose of this study was to determine the results of press-on nails with the water marble technique, the results of press-on nails with the marble drawing technique, and a comparison of the results of press-on nails with the water marble and drawing techniques. This study employed a quantitative approach and used an experimental research design. The results of press-on nails with water marble and drawing were assessed using a questionnaire with four aspects: design suitability, surface evenness, neatness of the finished result, and preference. Faux Nail Studio customers who like nail art and are and are and are aged 18 to 30 years were the subjects of this study who came to Faux Nail Studio on February 28, 2025. The data obtained from the questionnaire were processed using IBM SPSS 27. The t-test was used to determine the comparison of the finished results of press-on nails with the water marble and marble drawing techniques, and the average test was used to determine the finished results of each technique. The results of the study showed that (1)he finished results of press-on nails with the water marble technique had an average value of 2.96 out of 4, (2) the finished results of press-on nails with marble drawing had an average value of 3.68 out of 4, and (3) there was a significant difference between the two techniques, with a significance value of 0.000 < 0.05. (3) According to the panelists, the suitability of the design, surface flatness, and neatness of the results were 2.96 for the water marble technique and 3.68 for the marble drawing technique. (4) The panelists preferred the finished results of press-on nails with the marble drawing technique to the water marble technique.